A GLOBÁLIS ERŐFORRÁSOK HASZNOSÍTÁSA A PEDAGÓGIAI MUNKÁBAN A MESTERSÉGES INTELLIGENCIA SEGÍTSÉGÉVEL - Utasi, Eszter (Kultúratudományi Szemle, 2025)
Utilising Global Resources in Pedagogical Work with the Help of Artificial Intelligence The 21st century is a modern world, and artificial intelligence is needed in more and more areas. People value personal, social and psychological relationships. Human-tohuman cooperation and emotional relationships are essential for students and teachers in a public education institution. A research team from the Cornelius Research Institute is investigating the emotional intelligence of 5–9-year-olds using an online EQ test. However, everything is out of the ordinary when AI is introduced in the classroom and in the leisure time slot. Why does everything change? The human and the designed machine cannot connect, and the necessary interaction cannot occur. The lack of personal contact and sociality makes the knowledge transfer process completely different because it becomes impersonal. The importance of comprehension and meaning is repeated in the text. With the emergence of AI, the body of knowledge is multiplied, and the learners will have a vast body of knowledge. In addition to learners, teachers can also benefit from AI in the teaching process. AI in education can help teachers who are increasingly eager to take on administrative tasks in various ways. Students are still more open to receiving AI than teachers.